2022
DOI: 10.1021/acs.analchem.1c05309
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive Label-Free DNA Detection Based on Solution-Gated Graphene Transistors Functionalized with Carbon Quantum Dots

Abstract: Developing highly sensitive, reliable, cost-effective label-free DNA biosensors is challenging with traditional fluorescence, electrochemical, and other techniques. Most conventional methods require labeling fluorescence, enzymes, or other complex modification. Herein, we fabricate carbon quantum dot (CQD)-functionalized solution-gated graphene transistors for highly sensitive label-free DNA detection. The CQDs are immobilized on the surface of the gate electrode through mercaptoacetic acid with the thiol grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 65 publications
0
19
0
Order By: Relevance
“…It is equivalent to applying an offset voltage ( V offset ) in the gate electrode. The V offset can be expressed by the following equation , V offset = normalΔ q C where the amount of charge change (Δ q ) is induced by the hybridization of target RNAs, and C is the total capacitance of the SGGT. According to eq , V offset is determined by the total charges of the target RNA specifically recognized with Cas13a RNPs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is equivalent to applying an offset voltage ( V offset ) in the gate electrode. The V offset can be expressed by the following equation , V offset = normalΔ q C where the amount of charge change (Δ q ) is induced by the hybridization of target RNAs, and C is the total capacitance of the SGGT. According to eq , V offset is determined by the total charges of the target RNA specifically recognized with Cas13a RNPs.…”
Section: Resultsmentioning
confidence: 99%
“…It is equivalent to applying an offset voltage (V offset ) in the gate electrode. The V offset can be expressed by the following equation 39,40…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The device exhibited excellent sensing capability with a detection limit down to 1 nM and high specificity against noncomplementary DNAs. Another study has shown that the functionalization of CQDs with the graphene channel surface in the SG-GFET configuration exhibits detection of DNA with much higher sensitivity down to 1 aM concentration (Figure E) . In this work, the CQDs were immobilized on the graphene surface through mercaptoacetic acid to form the thiol group, and then the ssDNA probe was immobilized on CQD via π–π stacking interactions (lower panel in Figure E).…”
Section: Gfet Biosensors For Nucleic Acid Detectionmentioning
confidence: 80%
“…Another study has shown that the functionalization of CQDs with the graphene channel surface in the SG-GFET configuration exhibits detection of DNA with much higher sensitivity down to 1 aM concentration (Figure 4E). 112 In this work, the CQDs were immobilized on the graphene surface through mercaptoacetic acid to form the thiol group, and then the ssDNA probe was immobilized on CQD via π−π stacking interactions (lower panel in Figure 4E). Hybridization of target ssDNA with the ssDNA probe leads to the formation of dsDNA, resulting in the shift of V Dirac .…”
Section: ■ Structure and Function Of Fet And Gfetmentioning
confidence: 99%
“…There is a certain amount of conjugated sp 2 carbon segments in CDs, so most CDs possess good electrical conductivity and an excellent photoelectric conversion capability, favoring charge transport, exciton separation and sensing improvement. 29 In early work, a field-effect transistor (FET) device of glucose-derived CQDs showed ambipolar behaviors, with electron and hole mobilities as high as 8.49 × 10 −5 and 3.88 × 10 −5 cm 2 V −1 s −1 . The carrier mobility is also dependent on the length of the ligand attached to the CQDs.…”
Section: Structural and Surface Characteristics Of Carbon Dotsmentioning
confidence: 99%